EXPLORING SELF-EFFICACY OF PBL STUDENTS DOING PART-TIME JOB - Amiruddin Amiruddin; Tiaraaprillia Tiaraaprillia (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
The present study was accomplished to find out the process of self-efficacy on doing part-time job and to find out the level of self- efficacy students during part-time job. This research was completed by using a qualitative approach. Six semester eight Pendidikan Biologi students of 2019-2020 academic years chosen to be involved in this study. Semi-structured interview was employed as instrument to answer two research questions: what are the characteristics of students who have high self-efficacy while doing part-time job? And how many processes of self-efficacy work are for students doing part- time job? From the research, it was found that there were several characteristics of students who have high self-efficacy. First, to look at the problem more as a challenge to be solved than as an obstacle in achieving the goals and second, to have a strong commitment to achieve the goals set. Moreover, it is classified into four processes of self-efficacy; cognitive process, motivational process, affective process, selection process. Every participant has a different process to have a high self-efficacy, and every participant has many activities; starting from studying in college, doing more than one part-time job, and joining inside and outside organizations. All students also agreed that doing a part-time job was beneficial for them.